Peran Subsektor Perikanan dalam Pembangunan Wilayah dan Strategi Pengembangannya di Kabupaten Dairi - Saragih, Jef Rudiantho; Lela, Janidar; Harmain, Ummu (Jurnal Ilmiah Membangun Desa dan Pertanian, 2021)
Dairi Regency has natural and human resources and supports relatively adequate facilities, but fisheries do not significantly contribute to the regional economy. This study aims to describe the condition of fishing, analyze the role of the fishery subsector, and offer strategies for developing the fishery subsector. The research was conducted in Dairi Regency with 65 fish cultivators samples as the primary data source. Data and information were obtained through FGD from 7 resource persons from specialized agencies, the legislative, and other stakeholders in the fisheries subsector. Secondary data were obtained from several relevant institutions. The current condition of fisheries was analyzed descriptively, the role of the fishery sector was analyzed by Location Quotient, and development strategies were analyzed through SWOT analysis. In the 2010-2017 period, the fishery subsector contributed 2.10% to Dairi Regency's GDP. The most significant fish production is obtained from aquaculture in ponds, Minapadi, and floating nets. Capture fisheries come from lakes and rivers. The fishery subsector is a non-basic activity (LQ=0.97). Aquaculture is a primary activity with LQ=2.19, while capture fisheries are non-basic (LQ=0.49). Fishery development can be planned with a diversification strategy through: increasing utilization of natural and human resources and institutions to improve the efficiency of feed procurement and control of fish diseases; making local policies to improve the competitiveness of fisheries; and diversifying the fishery into Minapadi, ponds, and rivers; and lake capture fisheries. Regional strength can be optimized to respond to opportunities through the strategies: increasing fish production; responding to increased fish consumption as consumer demand; making policies that support institutional capacity building based on entrepreneurial activities, and improving the experience of fish cultivators and facilities and infrastructure.